MicroRNA-93 promotes cell growth and invasion in nasopharyngeal carcinoma by targeting disabled homolog-2. Issue 2 (28th July 2015) - Xu, Ya-Fei; Mao, Yan-Ping; Li, Ying-Qin; Ren, Xian-Yue; He, Qing-Mei; Tang, Xin-Ran; Sun, Ying; Liu, Na; Ma, Jun
Highlights: MiR-93 is upregulated in nasopharyngeal carcinoma cell lines and clinical tissues. Inhibition of miR-93 suppresses NPC cell growth, invasion and migration in vitro . Depletion of miR-93 suppresses NPC tumor growth in vivo . Disabled homolog-2 (Dab2) is verified as a miR-93 target gene. Dab2 was involved in miR-93-regulated NPC cell growth, invasion and migration. Abstract: Dysregulation of microRNAs (miRNAs) has been demonstrated to contribute to malignant progression in nasopharyngeal carcinoma (NPC). We previously reported that miR-93 was significantly upregulated in NPC based on a microarray analysis. However, the potential role and mechanism of action of miR-93 in the initiation and progression of NPC remain largely unknown. Quantitative RT-PCR demonstrated that miR-93 was significantly upregulated in NPC cell lines and clinical specimens. The MTT assay, colony formation assay, anchorage-independent growth, and Transwell migration and invasion assays showed that depletion of miR-93 inhibited NPC cell growth, invasion and migration in vitro and suppressed tumor growth in vivo . Disabled homolog-2 ( Dab2 ) was verified as a miR-93 target gene using Luciferase reporter assays, quantitative RT-PCR and Western blotting and was involved in miR-93-regulated NPC cell growth, invasion and migration. These results indicated that miR-93 plays an important role in the initiation and progression of NPC by targeting Dab2 and the miR-93/ Dab2 pathway may contribute to the development of novel therapeutic strategies for NPC in the future.